Stellar populations in KDCs of Sa galaxies - Falcn-Barroso, J; Bacon, R; Cappellari, M; Davies, R; De Zeeuw, P; Emsellem, E; Krajnović, D; Kuntschner, H; McDermid, R; Peletier, R; Sarzi, M; Van De Ven, G (2006)
We present integral-field observations of kinematically decoupled components (KDCs) in a sample of 24 Sa galaxies part of the SAURON Survey. We show how the V/ maps can be used to highlight the presence of the KDC and investigate their stellar populations (i.e. age) to understand their origin (i.e. secular vs hierarchical scenarios). We find that KDCs can be long-lived and are typically well aligned with the galaxies kinematical major axis, supporting mounting evidence that secular evolution becomes important at intermediate redshifts. Dynamically colder ones seem to host younger stellar populations. We also relate these features to the ones found in our sample of 48 elliptical and lenticular galaxies. We find that there is no age vs size relation for these decoupled components in Sa galaxies, suggesting that the dominant factor determining their size is the amount of star formation they have been subject to during their life time. © 2007 International Astronomical Union.